﻿A new species of the Cyrtodactylus brevipalmatus group (Squamata, Gekkonidae) from the uplands of western Thailand - L. Lee Grismer; Attapol Rujirawan; Siriwadee Chomdej; Chatmongkon Suwannapoom; Siriporn Yodthong; Akrachai Aksornneam; Anchalee Aowphol (ZooKeys, 2023)
An integrative systematic analysis recovered a new species of the Cyrtodactylus brevipalmatus group from the uplands of Thong Pha Phum National Park, Kanchanaburi Province in western Thailand. Cyrtodactylus thongphaphumensis sp. nov. is deeply embedded within the brevipalmatus group, bearing an uncorrected pairwise sequence divergence of 7.6–22.3% from all other species based on a 1,386 base pair segment of the mitochondrial NADH dehydrogenase subunit 2 gene (ND2) and adjacent tRNAs. It is diagnosable from all other species in the brevipalmatus group by statistically significant mean differences in meristic and normalized morphometric characters as well as differences in categorical morphology. A multiple factor analysis recovered its unique and non-overlapping placement in morphospace as statistically significantly different from that of all other species in the brevipalmatus group. The description of this new species contributes to a growing body of literature underscoring the high degree of herpetological diversity and endemism across the sky-island archipelagos of upland montane tropical forest habitats in Thailand, which like all other upland tropical landscapes, are becoming some of the most imperiled ecosystems on the planet.